Assembly and disassembly of branched ubiquitin chains - Gregor, Justin B.; Xu, Dantong; French, Michael E. (Frontiers in Molecular Biosciences, 2023)
Protein ubiquitylation is an essential post-translational modification that regulates nearly all aspects of eukaryotic cell biology. A diverse collection of ubiquitylation signals, including an extensive repertoire of polymeric ubiquitin chains, leads to a range of different functional outcomes for the target protein. Recent studies have shown that ubiquitin chains can be branched and that branched chains have a direct impact on the stability or the activity of the target proteins they are attached to. In this mini review, we discuss the mechanisms that control the assembly and disassembly of branched chains by the enzymes of the ubiquitylation and deubiquitylation machinery. Existing knowledge regarding the activities of chain branching ubiquitin ligases and the deubiquitylases responsible for cleaving branched chains is summarized. We also highlight new findings concerning the formation of branched chains in response to small molecules that induce the degradation of otherwise stable proteins and examine the selective debranching of heterotypic chains by the proteasome-bound deubiquitylase UCH37.